2017
DOI: 10.1099/mic.0.000501
|View full text |Cite
|
Sign up to set email alerts
|

Development of a CRISPR/Cas9-mediated gene-editing tool in Streptomyces rimosus

Abstract: Clustered regularly interspaced short palindromic repeats, associated proteins (CRISPR/Cas), has been developed into a powerful, targeted genome-editing tool in a wide variety of species. Here, we report an extensive investigation of the type II CRISPR/Cas9 system for targeted gene editing in Streptomyces rimosus. S. rimosus is used in the production of the antibiotic oxytetracycline, and its genome differs greatly from other species of the genus Streptomyces in the conserved chromosome terminal and core regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…10 Since its release, pCRISPomyces-2 has been successfully employed by other groups to edit the genome of various streptomycetes, demonstrating its potential for the engineering of both established hosts and other less commonly used strains. 17,[24][25][26][27][28][29][30][31] For instance, Hutchings and collaborators used it to generate both one-gene and whole-cluster deletions in Streptomyces formicae to conrm the identity of the antibiotic formicamycin (5) BGC and study the activity of the clusterincluded halogenase ForV. 25 The plasmid pCRISPomyces-2 was also employed by Zhang and colleagues to generate pointmutations and small deletions to increase oxytetracycline (6) production in Streptomyces rimosus, 26 as well as by Metsä-Ketela and colleagues to investigate glycosylation of the nucleoside antibiotic showdomycin (7) in Streptomyces showdoensis.…”
Section: Pcrispomyces Plasmids From Zhao and Colleagues 10mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Since its release, pCRISPomyces-2 has been successfully employed by other groups to edit the genome of various streptomycetes, demonstrating its potential for the engineering of both established hosts and other less commonly used strains. 17,[24][25][26][27][28][29][30][31] For instance, Hutchings and collaborators used it to generate both one-gene and whole-cluster deletions in Streptomyces formicae to conrm the identity of the antibiotic formicamycin (5) BGC and study the activity of the clusterincluded halogenase ForV. 25 The plasmid pCRISPomyces-2 was also employed by Zhang and colleagues to generate pointmutations and small deletions to increase oxytetracycline (6) production in Streptomyces rimosus, 26 as well as by Metsä-Ketela and colleagues to investigate glycosylation of the nucleoside antibiotic showdomycin (7) in Streptomyces showdoensis.…”
Section: Pcrispomyces Plasmids From Zhao and Colleagues 10mentioning
confidence: 99%
“…17,[24][25][26][27][28][29][30][31] For instance, Hutchings and collaborators used it to generate both one-gene and whole-cluster deletions in Streptomyces formicae to conrm the identity of the antibiotic formicamycin (5) BGC and study the activity of the clusterincluded halogenase ForV. 25 The plasmid pCRISPomyces-2 was also employed by Zhang and colleagues to generate pointmutations and small deletions to increase oxytetracycline (6) production in Streptomyces rimosus, 26 as well as by Metsä-Ketela and colleagues to investigate glycosylation of the nucleoside antibiotic showdomycin (7) in Streptomyces showdoensis. 27 As well as for generating deletions, 10 the same authors who developed pCRISPomyces-2 later used this plasmid for the precise insertion of single or bidirectional heterologous promoters to activate silent BGC in S. albus, S. lividans, Streptomyces roseosporus, S. venezuelae and S. viridochromogenes.…”
Section: Pcrispomyces Plasmids From Zhao and Colleagues 10mentioning
confidence: 99%
“…Restriction enzymes were obtained from New England Biolabs. Protospacers were first inserted into pCRISPomyces-2 plasmids [29] via BbsI-mediated Golden Gate assembly before the respective homology flanks were inserted via Gibson assembly. The protocol for plasmid construction was previously described [70].…”
Section: Construction Of Genome Editing Plasmidsmentioning
confidence: 99%
“…Advances in DNA sequencing and sequence analysis have driven deeper genomic insights into streptomycetes [25,26]. In addition, genetic engineering of previously challenging strains is now possible with CRISPR-Cas9 [27][28][29][30][31]. Combining the understanding of biosynthetic gene clusters (BGCs) and improved ability to edit streptomycete genomes, combinatorial engineering of analogue libraries for the purpose of producing a final therapeutically relevant product can now be accomplished at a faster pace.…”
Section: Introductionmentioning
confidence: 99%
“…As a type of fast and high-throughput genome editing tools, CRISPR-based systems have been widely employed for fundamental research and development of advanced cell factories in the microbial systems, such as Escherichia coli, Saccharomyces cerevisiae, and Streptomyces (18)(19)(20)(21). Previous studies have demonstrated that the Streptococcus pyogenes CRISPR-Cas9 system (SpCas9) can be utilized for high-efficiency multiplex genome editing by homologous recombination (HR)-or nonhomologous end joining (NHEJ)-mediated double-strandbreak (DSB) repair and reversible transcriptional gene expression in multiple model and industrial Streptomyces species (22)(23)(24)(25)(26)(27). However, SpCas9-based DNA editing has some shortcomings to be addressed.…”
mentioning
confidence: 99%